Childhood Legal Protection in Kazakhstan - APAKHAYEV, Nurlan; ADILOVA, Kultay; BUGYBAY, Dina; MUKALDYEVA, Gulyiya; MUKHAMADIYEVA, Gulzhan N.; KOSHPENBETOV, Bakhytkali M. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The article is dedicated to the analysis of formation, establishment, legislative bases of securing and realization of the rights of the child. Within the framework of the research, have been identified conditions and prospects for improving legislation on the implementation of child rights. The research was carried out using the general scientific dialectic method of cognition of social processes and particular methods of the system approach: structural-functional, concrete-historical, formal-logical, comparative-legal analysis and classification method. The analysis covers a complex of issues and is based on the achievements of legal science, statistical data, and relevant expert assessments. The theoretical and practical significance of the work is that the findings, generalizations and recommendations can be used to improve legislation in the field of protecting children's rights, to develop targeted programs; in scientific research on the problems of institutionalization and the mechanism for implementing public policies to protect the rights of children. The materials and conclusions of the study can be useful for specialists from governmental, political and non-governmental organizations in the further development of government programs and measures aimed at the effective enforcement of the child’s rights.